PsycEXTRA Dataset 2001
DOI: 10.1037/e462652006-001
|View full text |Cite
|
Sign up to set email alerts
|

Women at Altitude: Effect of Menstrual-Cycle Phase on Acute Mountain Sickness During Deployment to High Altitude Terrain

Abstract: m DISCLAIMERApproved for public release; distribution is unlimited.The views, opinions and/or findings in this report are those of the authors, and should not be construed as an official Department of the Army position, policy or decision, unless so designated by other official documentation.The investigators have adhered to the policies for protection of human subjects as prescribed in Army Regulation AR 70-25.Citations of commercial organizations and trade names in this report do not constitute an official D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…We also found no When comparing the frequency and severity of signs and symptoms of AMS in our study to the results from three previous studies on individuals residing at 4,300 m for 3-wk (Table 11), we found that intermittent exposures to 4,300 m were equally as effective as chronic altitude residence in eliminating the severity and frequency of AMS. The incidence of AMS (i.e., 50%) in our study was comparable to the mean results reported in other studies at this altitude (31,59,84,85). The highest AMS-C score in our study occurred at 12-h post exposure and was comparable to the mean highest AMS-C score reported from these four chronic altitude residence studies (Table 11).'…”
Section: "St-co T-t-+1supporting
confidence: 81%
“…We also found no When comparing the frequency and severity of signs and symptoms of AMS in our study to the results from three previous studies on individuals residing at 4,300 m for 3-wk (Table 11), we found that intermittent exposures to 4,300 m were equally as effective as chronic altitude residence in eliminating the severity and frequency of AMS. The incidence of AMS (i.e., 50%) in our study was comparable to the mean results reported in other studies at this altitude (31,59,84,85). The highest AMS-C score in our study occurred at 12-h post exposure and was comparable to the mean highest AMS-C score reported from these four chronic altitude residence studies (Table 11).'…”
Section: "St-co T-t-+1supporting
confidence: 81%
“…An attempt was made to address some of these problems by administering the ESQ-III using a computer software program, but this program was not validated against the paper and pencil version (Fulco et al, 1985). Although a shorter (5-item) paper and pencil questionnaire to assess AMS (Lake Louise [LL] AMS Scoring System) exists and has been validated against the ESQ-III (Savourey et al, 1995;Maggiorini et al, 1998), the LL questionnaire tends to overestimate AMS compared to the ESQ-III (Rock et al, 2001;Bartsch et al, 2004). To eliminate the administrative problems with the paper and pencil ESQ-III and overestimation of AMS by the LL questionnaire, a shortened (11-item) version of the ESQ was developed that could be administered on a hand-held computer.…”
Section: Introductionmentioning
confidence: 98%
“…The incidence of AMS does not differ by gender (Hackett and Roach, 2001;Bartsch and Swenson, 2013) and the phase of the menstrual cycle does not influence the incidence of AMS in women (Rock, 2001). However, healthy premenopausal women have fewer apneic-hypopneic events during sleep than healthy men at high altitude (Caravita et al, 2014).…”
Section: Acute Mountain Sickness (Ams)mentioning
confidence: 96%